2011
DOI: 10.1136/ard.2011.149807
|View full text |Cite
|
Sign up to set email alerts
|

Nottingham knee osteoarthritis risk prediction models

Abstract: Objectives (1) To develop risk prediction models for knee osteoarthritis (OA) and (2) to estimate the risk reduction that results from modifi cation of potential risk factors. Method This was a 12-year retrospective cohort study undertaken in the general population in Nottingham, UK. Baseline risk factors were collected by questionnaire. Incident radiographic knee OA was defi ned by Kellgren and Lawrence (KL) score ≥2. Incident symptomatic knee OA was defi ned by KL ≥2 plus knee pain. Progression of knee OA wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
150
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(160 citation statements)
references
References 32 publications
10
150
0
Order By: Relevance
“…Kneeling was investigated by four studies 18,21,32,34 and found to be significantly related to knee OA by three 18,21,32 , suggesting that it is an important element of physical work that can be classed as a risk factor for knee pain and knee OA. Lifting was also assessed by three studies 21,32,34 and was significantly related to knee OA by one 32 .…”
Section: Occupational Risksmentioning
confidence: 99%
See 1 more Smart Citation
“…Kneeling was investigated by four studies 18,21,32,34 and found to be significantly related to knee OA by three 18,21,32 , suggesting that it is an important element of physical work that can be classed as a risk factor for knee pain and knee OA. Lifting was also assessed by three studies 21,32,34 and was significantly related to knee OA by one 32 .…”
Section: Occupational Risksmentioning
confidence: 99%
“…One paper did not include enough information to be included in the meta-analysis 32 . There was consistent evidence that females were at higher risk of knee OA.…”
Section: Female Gendermentioning
confidence: 99%
“…Adjustments were performed for well-known (HR-1) and proposed predictors (HR-2) of KR in OA. Choices of confounders were made according to the prediction models proposed by Kerkhof et al and in line with other similar reports [5][6][7]22]. The first model (HR-1) includes adjustments for age, gender and BMI.…”
Section: Analysis Planmentioning
confidence: 99%
“…A potential solution to this limitation has been provided by another group: the 'Nottingham knee prediction models' are mathematical models designed to apply what we know about key OA risk factors to predict incident, symptomatic or progressive (increase by K/L grade 1) OA of the knee [Zhang et al 2011]. For example, the equation for incidence of symptomatic OA is Logit = −7.733 + 0.56 age + 0.29 female + 0.089 BMI + 0.245 occupational risks + 0.543 family history + 0.87 knee injury.…”
Section: Safety (S)mentioning
confidence: 99%